Fat versus Lean Mass Ratio: A New Anthropometric Indicator in Predicting Metabolic Syndrome Among UniSZA Malay Students - Wee, Bee Suan; Lim, Jing Ying (2019)
This study aimed to address the literature gap on the interactive effect of fat mass (FM) and lean body mass (LBM) by developing a cut-off value for fat versus lean mass ratio (FLMR) in predicting MS; and to investigate the association between this indicator with MS and its components. Subjects comprised 238 Malay adolescents (?% male, ?% female) aged 18 to 19 years old. Anthropometric comprised weight, height and wasit circumference. Body composition was measured using bioelectrical impedance analysis (BIA) techniques and blood pressure was measured. Fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-c), low-density lipoproteincholesterol (LDL-c) were determined from an overnight fasting blood sample. MS was diagnosed based on IDF (2007) definition for adolescents aged 16-year-old and above. Receiver Operating Characteristics (ROC) curve analysis revealed that the optimal cut-off value for FLMR was 0.441 with AUC of 0.874 (95% CI: 0.825, 0.913). FLMR were significantly associated with high WC (p<0.001), low HDL-c (p<0.001) and MS (p<0.05). However, there were no significant association between hypertension, hyperglycaemia and hypertriglyceridemia with FLMR. Binary Logistic Regression analysis revealed that adolescents with high WC, low HDL-c and MS, respectively had 43.4 (95% CI: 9.7,193.9), 4.7 (95% CI: 2.3,9.8) and 13.3 (95% CI: 1.5,121.2) odds of developing FLMR higher than cut-off value. In conclusion, FLMR possess good discriminatory ability in predicting MS among adolescents. Significant association exists between FLMR with MS and some of its components. Intervention programme is needed urgently to reduce the level of body adiposity among UniSZA Malay students.